Brittany Jackson: capstone - Jackson, Brittany, artist (Colorado State University. Libraries, 2016)
The artist's statement: As a graphic artist, my work is inspired by the tension between organic forms and structured design. While growing up in Colorado, I loved spending time outside in the vast, colorful mountains ranges. The natural geometry found behind a small flower up to the structure of the entire universe is fascinating to me. My curiosity motivates me to explore the world and share my thoughts and ideas creatively. The influence of natural forms and geometry can be found in a lot of pieces of my work. I typically prefer simple design, and abstracting complex forms and emotions to minimal concepts. Working in different artistic mediums influence each other by exercising the different creative sides of my brain. I primarily work in vector illustration and typography, but I also enjoy photography, pottery, and playing the violin.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design